Secondary efficacy results from a phase 3 study comparing efficacy and safety of biosimilar candidate ABP 215 with bevacizumab in patients with non-squamous non-small cell lung cancer (NSCLC) - Thatcher, Nicholas; Thomas, Michael (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: ABP 215 is a biosimilar candidate to bevacizumab, a VEGF inhibitor. Analytical, functional and pharmacokinetic similarity assessments between ABP 215 and bevacizumab have been completed. Here we present results of secondary efficacy variables, focusing on the risk difference (RD) of the overall response rate (ORR) and progression-free survival (PFS). Primary efficacy and safety results from this phase 3 study have been previously reported.Methods: In this randomized, double-blind, active-controlled study in adults with NSCLC receiving first-line chemotherapy with carboplatin and paclitaxel, patients were randomized (1:1) to receive 15 mg/kg of the investigational product (IP) (ABP 215 or bevacizumab) administered as an IV infusion every 3 weeks for 6 cycles. Patients remained on treatment until 21 days after the last dose of IP or...